Application of biological welding as a method of treatment of esophageal metaplasia - V. V. Tyselskyi; B. G. Bondarchuk; V. A. Hordovskyi; A. B. Kebkalo (Клінічна хірургія)
Objective. To estimate a high-frequency welding of the living tissues as a variant of treatment for the Barrett’s esophagus.